Analisis Implementasi Kebijakan E-Retribusi Pasar Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Karanganyar - Dian Ambarwati; Suhesti Ningsih; Indra Lila Kusuma (ITB AAS INDONESIA, 2024)
This research aims to determine and analyze the implementation of payment procedures, deposits and places of payment of retribution manually & electronically and obstacles encountered when implementing e-retribution. This research is descriptive research with a qualitative approach. The types of data used in this research are primary data and secondary data. The data collection techniques used were obtained by means of field research and library research. Data analysis was carried out using qualitative analysis and using purposive sampling techniques to determine sources. The research results show that the implementation of the electronic levy collection policy at the Department of Trade, Industry and Manpower has not been implemented optimally. In terms of implementation techniques, there are problems with machine damage, network errors, and cards that are not stored properly so they cannot be swiped on the machine. There is a shortage of resources to manage levy receipts electronically. Apart from that, there is a lack of awareness among traders regarding electronic payments. E-retribution has not been implemented completely because electronic collection is still not efficient because there are still obstacles encountered.